Associations of Early Developmental Milestones With Adult Intelligence. Issue 2 (15th February 2017) - Flensborg‐Madsen, Trine; Mortensen, Erik L.
Abstract : The study investigated whether age at attainment of 20 developmental milestones within the areas of language, walking, eating, dressing, social interaction, and toilet training was associated with adult intelligence. Mothers of 821 children of the Copenhagen Perinatal Cohort recorded 20 developmental milestones at a 3‐year examination, and all children were administered the Wechsler Adult Intelligence Scale when they were 20–34 years old. Later attainment of a number of milestones was associated with lower adult IQ with the strongest associations found for those related to language and social interaction. The adjusted full‐scale IQ means were 107.0, 101.8, and 100.6 for being able to form a sentence at less than 24 months, at 24 months, and later than 24 months.